When did Argentina lose its mojo? A short note on economic divergence - Sebastián Katz; Eduardo Levy Yeyati (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2024)
Based on long series of per capita GDPs, we characterize the economic divergence of Argentina in the 20th century relative to a group of countries with comparable initial income per capita. We find the divergence to be considerably longer than usually conjectured, with two marked tranches in the first half of the century and in the post war period, the latter being associated with GDP underperformance despite the relative decline in population. We identify specific dates for the inflection points, discuss the context in each case, and propose a potential explanation of the divergence together with a description of the highly volatile plateau displayed since the 1990s.
Keywords: 330